TANGGUNGJAWAB HUKUM DOKTER TERHADAP PASIEN DI KAMAR BEDAH - Arifin, Jajang (Yustitia, 2022)
The relationship between doctors and patients has been going on for a long time. A doctoris considered to be someone who gives treatment to people who need it. The legalrelationship between doctors and patients begins with a paternalistic vertical relationshippattern like father and son which departs from the principle of "Father knows best" wherea doctor is considered to be more aware and able to treat the disease suffered by thepatient. The position of doctors is higher than the position of patients and doctors have animportant role in their development. When viewed from the relationship between thedoctor and the patient, the doctor as a professional, with his education and experience isexpected to be able to use his knowledge carefully and responsibly so that he does notbecome negligent, while a patient with a weak position, does not know whether the actionstaken by the doctor are correct or not, can trust and leave the measures for his health tothe doctor, based on the information obtained from the doctor. Such a pattern ofrelationships between doctors and patients has gradually shifted towards a moredemocratic one, namely a horizontal contractual relationship or Joint participation.